2010
DOI: 10.1002/esp.1941
|View full text |Cite
|
Sign up to set email alerts
|

Electrical imaging of sliding geometry and fluids associated with a deep seated landslide (La Clapière, France)

Abstract: International audienceThis paper deals with the applicability of electrical resistivity tomography (ERT) for the recognition of large landslide structures at depths, which have never previously been imaged accurately. One of the most studied and instrumented deep landslides in Europe is taken as an example: the La Clapière landslide. The first stage of the study consisted of an accurate geological mapping taking into account a morphological analysis of gravitational deformations. This allowed a very fine defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 46 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…ERT has been widely applied to these types of problems and many recent studies have shown its usefulness in defining geological structure, fault geometry, landslide boundaries (sliding surfaces), and deep water circulations (Naudet et al, 2008;Fazzito et al, 2009;Heincke et al, 2010;Jomard et al, 2010;Lebourg et al, 2010;Pánek et al, in press). In this study, ERT was useful because of 1) the relatively simple geological structure of the La Marbrière slope (monoclinal layers and vertical faults) that would result in simple inverted models, and 2) high resistivity contrast between limestone and mudstone or a fault zone and limestone that facilitate identification of stratigraphic boundaries to evaluate fault offsets (Caputo et al, 2003;Nguyen et al, 2007;Adepelumi et al, 2008;Schrott and Sass, 2008;Gelis et al, 2010).…”
Section: Methodsmentioning
confidence: 98%
“…ERT has been widely applied to these types of problems and many recent studies have shown its usefulness in defining geological structure, fault geometry, landslide boundaries (sliding surfaces), and deep water circulations (Naudet et al, 2008;Fazzito et al, 2009;Heincke et al, 2010;Jomard et al, 2010;Lebourg et al, 2010;Pánek et al, in press). In this study, ERT was useful because of 1) the relatively simple geological structure of the La Marbrière slope (monoclinal layers and vertical faults) that would result in simple inverted models, and 2) high resistivity contrast between limestone and mudstone or a fault zone and limestone that facilitate identification of stratigraphic boundaries to evaluate fault offsets (Caputo et al, 2003;Nguyen et al, 2007;Adepelumi et al, 2008;Schrott and Sass, 2008;Gelis et al, 2010).…”
Section: Methodsmentioning
confidence: 98%
“…The first activity reported dates from the early 1930s, with a peak evolution between 1960 and 1990 leading to a 130 m-high scarp development in the middle of the slope. Thus, since the 1990s, structural investigations (Follacci 1987;Ivaldi 1991), geomechanicals triaxial experiments on rock samples, hydrogeological studies (Cappa et al 2004;Guglielmi et al 2005), numerical modelling and geophysical surveys (Lebourg et al 2005;Jomard et al 2007Jomard et al , 2010 have been performed underlining a complex post-failure behaviour. The La Clapière DSL is geometrically bound by N1108-1408E and N0108-0308E fault sets (Fig.…”
Section: Field Analysismentioning
confidence: 99%
“…As proved by other ERT surveys (e.g. Jomard et al, 2010;Saad et al, 2012;Gańko et al, 2013), water saturation could shift the conductivity values in the ERT images towards higher values; however, it does not substantially change the ERT images of geological structure formed by significantly different lithotypes.…”
Section: Dsgsds Reflected In Observations -Reliability Of Field Survementioning
confidence: 77%